EVALUATION OF BIOMEDICAL WASTE MANAGEMENT PRACTICES IN MULTI-SPECIALITY TERTIARY HOSPITAL - Srivastav, Shalini; Kariwal, Peeyush; Singh, Atul Kumar; Shrotriya, V P (Indian Journal of Community Health, 2010)
Background: Biomedical Waste (BMW,) collection and proper disposal has become a significant concern for both the medical and the general community The scientific “Hospital waste Management “is of vital importance as its improper management poses risks to the health care workers ,waste handlers patients, community in general and largely the environment. Objectives: (i) To assess current practices of Bio-medical Waste management including generation, collection, transportation storage, treatment and disposal technologies in tertiary health care center. (ii) To assess health andsafetypracticesfor the health care personnel involved in Bio-Medical waste Management. Materials and Methods: Waste management practices in tertiary care-centre was studied during May 2010 June 2010. The information/data regarding Bio-Medical Waste Management practices and safety was collected by way of semi structured interview, proforma being the one used for WASTE AUDITING QUESTIONNAIRE. The information collected was verified by personal observations of waste management practices in each ward of hospital. Results : SRMS-IMS generates 1. 25Kgs waste per bed per day and maximum waste is generated in wards. The institute has got separate color coded bins in each ward for collection of waste but segregation practices needs to be more refined. The safety measures taken by health care workers was not satisfactory it was not due to unavailability of Personal protective measures but because of un-awareness of health hazards which may occur due to improper waste management practices. Thus it is concluded that there should be strict implementation of a waste management policy set up in the institute, training and motivation must be given paramount importance to meet the current needs and standard of bio-medical waste management.